Paradoxical septal motion: A diagnostic approach and clinical relevance. Issue 2 (28th February 2018) - Clancy, David J.; Mclean, Anthony; Slama, Michel; Orde, Sam R.
Abstract: Abnormal septal motion (commonly referred to as septal bounce) is a common echocardiographic finding that occurs with several conditions, including the following: mitral stenosis, left bundle branch block, pericardial syndromes and severe pulmonary hypertension. We explore the subtle changes that occur on M‐mode imaging of the septum, other associated echocardiographic features, the impact of inspiratory effort on septal motion and relevant clinical findings. Finally, we discuss the impact of abnormal septal motion on cardiac form and function, proposing there is a clinically significant impact on biventricular filling and ejection.